Penerapan Konsep Green pada Sungai Maros - Aulia Hasanah; Shirly Wunas; Suriana La Tanrang (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2015)
Increased population density around the watershed and increased use or exploitation of natural resources intensively results in the condition of the watershed experiencing degradation. This study aims to analyze the condition of the building structure and the availability of infrastructure to the Green Concept along the river. This research was conducted using qualitative and quantitative analysis. From the results of the analysis it was found that the condition of the building layout and environment did not fully meet the standards / spatial policy if viewed based on the density of the building. The level of building density is classified as dense in terms of regional land use. The community tends to build houses in a group manner so that the settlement development pattern becomes irregular and congested. Conditions for the availability of supporting infrastructure The Green Concept has not been able to support the application of the concept due to the unavailability of pedestrian lanes and green lanes in the river border, the unavailability of MCK and waste management, and the unequal distribution of clean water. Green concept covers three main aspects, namely environmentally friendly transportation, environmentally friendly waste management, and environmentally friendly water management. the direction of applying the green concept is by rearranging the building with the majority of stilt houses standing on the riverbank by lifting the house then adjusting the distance between houses. Directions for houses to be built on vacant land, by arranging the size of the house with the distance between houses and improving the quality and availability of supporting infrastructure (existing).